Analisis Kualitas Pelayanan Fiskus Dalam Meningkatkan Kepatuhan Pelaporan Surat Pemberitahuan Tahunan (SPT) Wajib Pajak Orang Pribadi (Studi Kasus Kantor Pelayanan Pajak Pratama Majalaya) - Ridwan, Muhammad; Putri, Nadya Anggara (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2024)
Taxes are the main source of state revenue used to finance various development programs and public services. The success of tax collection is highly dependent on taxpayer compliance, both individuals and business entities. One of the factors that influence taxpayer compliance is the quality of service provided by tax authorities or tax officers at the tax office. This study aims to analyze the effect of the quality of fiscal services at the Majalaya Primary Tax Service Office (KPP) on individual taxpayer compliance in reporting Annual Tax Returns (SPT). Several previous studies have shown that taxpayer awareness and the quality of fiscal services have a positive effect on individual taxpayer compliance. The research method used uses a descriptive qualitative approach. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the effect of the quality of taxpayer services using the dimensions of reliability, tax information systems, internal and external supervision, and responsiveness has become an effective framework. Keywords: Tax, Fiscal Service Quality, Tax Return, KPP Pratama Majalaya